Realm Breaker - Book 1 - Aveyard, Victoria; Baraldi, Francesca (New York, NY : HarperTeen, an imprint of HarperCollinsPublishers, 2021)
"A strange darkness grows in Allward. Even Corayne an- Amarat can feel it, tucked away in her small town at the edge of the sea. She soon discovers the truth: she is the last of an ancient lineage--and the last hope to save the world from destruction. But she wont be alone. Even as darkness falls, she is joined by a band of unlikely companions. Together they stand against a vicious opponent, invincible and determined to burn all kingdoms to ash, and an army unlike anything the realm has ever witnessed."--
"Map art by Francesca Baraldi"--Title page verso.
Keywords: Imaginary wars and battles -- Juvenile fiction; Quests (Expeditions) -- Juvenile fiction; Magic -- Juvenile fiction; Imaginary wars and battles -- Fiction; Quests (Expeditions) -- Fiction; Magic -- Fiction